Intentions to reduce sugar-sweetened beverage consumption: the importance of perceived susceptibility to health risks. Issue 17 (21st December 2021) - Dono, Joanne; Ettridge, Kerry A; Wakefield, Melanie; Pettigrew, Simone; Coveney, John; Roder, David; Durkin, Sarah; Wittert, Gary; Martin, Jane; Miller, Caroline L
Abstract: Objective: There are numerous health effects associated with excess sugar-sweetened beverage (SSB) consumption. Interventions aimed at reducing population-level consumption require understanding of the relevant barriers and facilitators. This study aimed to identify the variables with the strongest relationship with intentions to reduce SSB consumption from a suite of variables derived from the literature. Design: Random-digit dialling of landline and mobile phones was used to survey adults using computer-assisted telephone interviews. The outcome variable was 'likelihood of reducing SSB consumption in next 6 months', and the predictor variables were demographics, SSB attitudes and behaviour, health risk perceptions and social/environmental exposure. Setting: Australia. Participants: A subsample of 1630 regular SSB consumers from a nationally representative sample of 3430 Australian adults (38 % female, 51 % aged 18–45 years, 56 % overweight or obese). Results: Respondents indicated that they were 'not at all' (30·1 %), 'somewhat' (43·9 %) and 'very likely' (25·3 %) to reduce SSB consumption. Multivariate nominal logistic regressions showed that perceiving future health to be 'very much' at risk was the strongest predictor of intention to reduce SSB consumption (OR = 8·1, 95 % CI 1·8, 37·0, P < 0·01). Other significant predictors ( P < 0·01) included self-perceptions about too much consumption, habitual consumption, difficulty reducing consumption and likelihood of benefitting from reduced consumption. Conclusions: Health risk perceptions had the strongest relationship with intentions to reduce consumption. Age and consumption perceptions were also predictors in the multivariate models, whereas social/environmental exposure variables were not. Interventions may seek to incorporate strategies to denormalise consumption practices and increase knowledge about perceived susceptibility to health risks.